AGITATION OF SIKHS AGAINST BRITISH IN COLONIAL PUNJAB: AN APPRAISAL OF GURDAWARA REFORM MOVEMENT - Dr. Anam Iftikhar; Dr. Muhammad Abrar Ahmad; Dr. Shumaila Firdos (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
In the twentieth century India was transitioning itself from traditional to modern country in terms of political and social change. It was a period of general renaissance in various spheres of life, religion, social and political customs. Indians were not only getting awareness about their political rights but they were also filled with the passion of nationalism which was being expressed by them at various times. If someone looks at the course of historical development of Indian Colonialism then it is easy to assess that in the start of twentieth century all India was experiencing the same passion. In this study an effort has been made to construct a narrative that this nationalism was not confined to only few castes or creeds, all Hindus, Muslims and Sikhs were showing vigorous reaction towards British policies. Particularly Sikh response was intricate and interesting as some Sikhs teamed up with the British, while others aggressively struggled against their rule. Therefore, this paper highlights the role of Sikh community against British in Punjab.